2004
DOI: 10.1590/s0034-89102004000700010
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts between employee preferences and ergonomic recommendations in shift scheduling: regulation based on consent is not sufficient

Abstract: ObjectiveContribution to the discussion of the role of participation/consent of employees in working hours regulation. Methods Exploratory analysis of conflicts between preferences of employees and ergonomic recommendations in shift scheduling by analysing a large number of participative shift scheduling projects. ResultsThe analysis showed that very often the pursuit of higher income played the major role in the decision making process of employees and employees preferred working hours in conflict with health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this respect, it is possible that, despite a reduction in workhours, the women in this study still experienced negative effects of a double burden and therefore became psychologically distressed. In this view, a potentially important confounder is whether changes in worktime arrangements were forced upon the employee, more likely leading to negative effects, or whether they were the worker's own choice, possibly leading to more positive effects (39,40). For example, an obligation to reduce the amount of workhours because of company restructuring can be an important source of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is possible that, despite a reduction in workhours, the women in this study still experienced negative effects of a double burden and therefore became psychologically distressed. In this view, a potentially important confounder is whether changes in worktime arrangements were forced upon the employee, more likely leading to negative effects, or whether they were the worker's own choice, possibly leading to more positive effects (39,40). For example, an obligation to reduce the amount of workhours because of company restructuring can be an important source of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations have to be weighed against the favorable aspects of flexibility for the worker, his/her family and social needs. Ergonomic changes in shift schedules should be chosen, which may be preventative and may reduce the incidence of late detrimental health effects [17,65,107,108].…”
Section: Adaptation Of Circadian Time Organization To the Night Shiftmentioning
confidence: 99%
“…Nursing and Health Sciences Research Consortium 2000;Ellis and Pompili 2002;West, Boughton, and Byrnes 2009) and occupational health and safety (cf. Siebenaler and McGovern 1991;Gartner 2004;Pisarski et al 2008). Similarly, the few studies that have reported nurses' views of shiftwork also predominantly report their dissatisfaction with shiftwork (cf.…”
mentioning
confidence: 99%
“…Nursing and Health Sciences Research Consortium 2000; Ellis and Pompili 2002; West, Boughton, and Byrnes 2009) and occupational health and safety (cf. Siebenaler and McGovern 1991; Gartner 2004; Pisarski et al. 2008).…”
mentioning
confidence: 99%